Environment-friendly nutrient supply in the area of NYÍRERDŐ Zrt - Marozsán, Marianna (Acta Agraria Debreceniensis, 2012)
The widespread realization of environmental friendly management is an important segment of seeking sustainable technological andtechnical solutions. The methods ensuring sustainable development by exploiting natural facilities have great significance. Bacteria-basedbiofertilizers and wood ash are good examples of them. Using bacteria-based biofertilizer means a kind of biofertilization that is using thepossibilities provided by the ecosystem.